An Analysis of English Language TEst Used at SMAN 1 Amonggedo - Gau, Evy Husnianti; Sale, Firdaus; Alberth, Alberth (Journal of Teaching English, 2019)
The main objective of this study was to analysis the quality of the test used involving the content validity, reliability, level of difficulty, and discrimination power. It Studied the quality of the English test, Especially English final test used for the first semester students’ at the first, second, and the third grade of SMAN 1 Amonggedo in academic year of 2017/2018. The source of the data in this study was the student’s answer sheet of first, second, and third grade of SMAN 1 Amonggedo. The total answer sheets of the students were 178.  In analyzing the data, the researcher used a formula to analyzed content validity and also used SPSS 16 program to measure the reliability, level of difficulty, and discrimination power. The result of the content validity analysis of the test in the three levels with two classes in each level showed that all of tests were fulfill the criteria of a good test because its representative from the syllabus. Second, the finding of reliability analysis showed that almost all items of test were valid. Indeed all of test has very high reliability because the number value of reliability 0, 70 < r11  ≤ 1. The level of difficulty analysis showed that 72, 5 % in the level of medium and only 27, 5% in the level of easy. Discrimination power analysis of the test had a good discrimination, with the number of percentage 46%. It also showed that 8,3% in  poor discrimination, 13,3% in the level of sufficient, 26,6% had very good or excellent discrimination, but there was also 5,8% item skipped.